Promoting Active Aging: Lessons Learned in an Implementation Pilot in Primary Care. Issue 2 (2nd October 2020) - Callahan, Kathryn E.; Willard, James; Foley, Kristie L.; Miller, Michael E.; Houston, Denise K.; Kritchevsky, Stephen B.; Williamson, Jeff D.; Applegate, William B.; Girma, Feben; Whitehead, Sarah E.; Rejeski, W. Jack
Abstract : BACKGROUND: Physical activity (PA) preserves mobility, but few practices screen older adults for mobility impairment or counsel on PA. DESIGN: "Promoting Active Aging" (PAA) was a mixed‐methods randomized‐controlled pilot, to test the feasibility and acceptability of a video‐based PA counseling tool and implementation into practice of two mobility assessment tools. SETTING: Three primary care practices affiliated with Wake Forest Baptist Health. PARTICIPANTS: Adults aged 65 years and older who presented for primary care follow‐up and were willing and able to answer self‐report questions and walk 4 meters (n = 59). INTERVENTION: Video‐based PA counseling intervention versus control video, "Healthy Eating." MEASUREMENTS: Potential participants completed mobility assessments: self‐report (Mobility Assessment Tool‐short form (MAT‐sf)) and performance based (4‐meter walk test). We assessed PAAʼs implementation—feasibility, acceptability, and value—via interviews and surveys. Effectiveness was measured via participant attendance at a PA information session. RESULTS: Of 92 patients approached, 89 (96.7%) agreed to mobility assessment. Eighty‐nine completed MAT‐sf, and 97.8% (87/89) completed 4‐meter walk test. Sixty‐seven (75%) met eligibility criteria, and 59 (88%) consented to be randomized either to the PA counseling intervention (Video‐PA) or to active control (Video‐C). Most participants viewed the walk test positively (51/59; 86.4%). Staff reported that completion of patient surveys, MAT‐sf, and videos required significant staff time and support (median = 26 minutes for all), resulting in low acceptability of MAT‐sf and the videos. Attendance at a PA information session did not differ by randomization group (Video‐PA = 11/29 (37.9%); Video‐C = 12/30 (40%); 95% confidence interval for difference in proportion = −0.29 to 0.25). CONCLUSIONS: Mobility assessment, particularly a 4‐meter walk test, was feasible in primary care. Tablet‐based assessment (MAT‐sf) and video counseling tools, selected to reduce staff effort, instead required significant time to implement. Future work to promote PA should identify effective ways to facilitate adoption of PA in sedentary older adults that do not burden staff.